Bringing The Secret Life Of Bees in Literature Class to Strengthen The Students Humanity - Muawwinatul Laili (ELite Journal : International Journal of Education, Language, and Literature, 2018)
This research is emphasized on the improving students character especially in their humanity character. In fact, there are many students do not realize that humanity decreases every day. Furthermore, they do not get some humanity aspects in their class because the lecturer only focuses on the teaching result. Here, the researcher tries to bring the humanity aspects in literature class exactly at Literary Criticism subject through Sue Monk Kidds The Secret Life of Bees. The students are English department students in the third semester of Nahdlatul Ulama University of Sidoarjo. The researcher leads the students to use genetic structuralism theory in analyzing the novel.  In this case, the researcher leads the students to see the literary work from two points of views namely intrinsic and extrinsicand connect directly the phenomena from that period of the literary works are created to the intrinsic element of the literary work itself.After the students find some information about the content of the novel and relate it to social phenomena that occurred in South Carolina in 1964. As the result, they find some racism action faced by Afro-Americans that are categorized in inhumanity attitude, they are; prejudice, segregation, discrimination, extermination, and expulsion. All of the attitudes show that the humanity is needed to teach to students in order to decrease racism and inequality in our life.Keywords:     secret life of bees, humanity, racism.